Meaning Construction of Good Looking in Public Relation Practitioners at Hotel Industries - Ade Tuti Turistiati; Yudi Sudiana; Adita Miranti (Universitas Multimedia Nusantara, 2023)
The profession of public relations (PR) is required in the hotel industry. Society frequently perceives a PR practitioner as having both technical and non-technical requirements, such as being good looking. In reality, one of the requirements for becoming a public relations officer in the hotel industry is that a person be good looking. The purpose of this study is to explore the construct meaning of good looking in hotel PR practitioners. Furthermore, the researchers examined the challenges that the hotel industry faces in obtaining good-looking PR, as well as solutions to these challenges. The theory of reality construction and symbolic interaction is used in this study, which employs a qualitative descriptive research method. According to the findings of the study, the definition of good looking is perceived as a myth that is spreading in society, namely beautiful/handsome with white skin, tall and slim. However, some interpret good-looking as more intellectual, which impacts job performance. Furthermore, when it comes to hotel public relations, hotel managers tend to prioritize physical appearance. It can be considered discrimination, dehumanization, and subordination.